Seasonal Flooding Causes Intensification of the River Breeze in the Central Amazon. Issue 10 (22nd May 2019) - Santos, Mercel J.; Medvigy, David; Silva Dias, Maria A. F.; Freitas, Edmilson D.; Kim, Hyungjun
Abstract: In the central Amazon, surrounding Manaus City, Brazil, the landscape dominated by forest and water bodies supports development of river breezes. Seasonal inundations modify this local scenery affecting, consequently, the local circulations. However, this effect has not properly been investigated yet. Thus, we carried out numerical experiments for a river breeze case to investigate the seasonal flooding effect on the river breeze and detail the processes involved in the river breeze development. In the numerical experiments, we ran the Catchment‐Based Macro‐scale Floodplain (CaMa‐Flood) model to simulate flooding depth and extent and used the CaMa‐Flood outputs to force the Ocean‐Land‐Atmosphere Model. The seasonal flooding alters the surface energy partitioning causing a temperature decrease over the river region and intensification of the river breezes in the daytime. The intensified river breezes propagate more rapidly through the upland region, take longer to dissipate and promote stronger upward vertical motion altering the heat and mass transport. These novel findings are fundamentally important to the understanding of the local climate variability of the central Amazon. We can infer that river breezes and its consequence to local climate are less (more) pronounced in drought (wet) years. Key Points: Different energy partitioning of the water and land surface triggers the river breezes in the central Amazon Seasonal flooding intensifies the river breezes by altering the surface energy partitioning The roughness variation between the floodplain and the upland regions has no clear influence on the displacement of the river breeze fronts